An Unusual Presentation of Kala-Azar in Bangladesh - Kabir, Ahmedul; Amin, Md. Robed; Bishwas, Aparna; Al-Amin, Mohammad; Mukerrama, Shegufta Mishket; Roy, Shanta; Barman, Swadesh (Bangladesh Journal of Medicine, 2013)
Bangladesh Journal of Medicine, Vol 24 No 1, 2013, Page 35-37 DOI: http://dx.doi.org/10.3329/bjmed.v24i1.15035